Radiotherapy is essential after complete response to asparaginase-containing chemotherapy in early-stage extranodal nasal-type NK/T-cell lymphoma: A multicenter study from the China Lymphoma Collaborative Group (CLCG). Issue 1 (October 2018) - Deng, Xiu-Wen; Wu, Jun-Xin; Wu, Tao; Zhu, Su-Yu; Shi, Mei; Su, Hang; Wang, Ying; He, Xia; Xu, Li-Ming; Yuan, Zhi-Yong; Zhang, Li-Ling; Wu, Gang; et al.
Abstract: Purpose: This study aimed to clarify the benefit of radiotherapy (RT) in patients with early-stage extranodal NK/T-cell lymphoma (NKTCL) who achieve a complete response (CR) after asparaginase-containing chemotherapy (CT). Patients and methods: Of 240 patients achieved a CR after asparaginase-containing CT, 202 patients received additional RT (CT + RT), and 38 patients did not (CT alone). Results: Compared to CT alone, CT + RT significantly improved overall survival (OS), disease-free survival (DFS) and locoregional control (LRC). The 5-year OS, DFS and LRC rates were 84.9%, 76.2% and 84.9% for CT + RT, compared to 58.9% ( P = 0.006), 43.6% ( P = 0.001) and 62.1% ( P = 0.026) for CT alone. The 5-year cumulative disease recurrence rate was 18.8% for CT + RT compared to 46.9% ( P = 0.003) for CT alone. High-dose RT (≥50 Gy) significantly decreased the risk of locoregional recurrence. The 5-year cumulative locoregional failure rate was 35.5% for patients receiving <50 Gy compared to 8.8% for patients receiving ≥50 Gy ( P = 0.028). Conclusions: For patients with early-stage NKTCL who achieve a CR after asparaginase-containing CT, omission of RT results in frequent locoregional recurrence and a poor prognosis; RT is essential to improve locoregional control and survival.